Prednisolone and salbutamol in the hospital treatment of acute asthma. Issue 3 (March 1994) - Connett, G J; Warde, C; Wooler, E; Lenney, W
Abstract : The use of oral prednisolone (2 mg/kg) to treat children admitted to hospital with acute asthma was assessed in a placebo controlled study. Children were further randomised to receive either 0.15 mg/kg salbutamol every 30 minutes for the first three hours of admission, or 5 mg salbutamol every one to four hours as needed. Treatment was double blind and the assessor was unaware of the nebuliser regimen given. Children were examined before and after treatment with salbutamol on arrival and reassessed four hours after admission. Seventy children completed the study. Seventeen (46%) of 37 children receiving prednisolone and six (9%) of 33 receiving placebo were fit for discharge after four hours of treatment. There was no significant difference between the two nebuliser regimens. Clinical parameters indicative of asthma severity were improved in all groups. Between group comparisons at reassessment showed higher peak flows in those receiving prednisolone and nebulisers every 30 minutes but differences were not significant for other parameters. Objective parameters indicating steroid efficacy over placebo were minimal. Despite this, those receiving prednisolone were more readily identifiable as being fit for discharge within four hours of treatment.